A Qualitative Study: Effectiveness of Learning Corners Approach to Foster Creativity in Preschoolers - Hanifah, Nor; Azizah, Dewi Maulana; Muzaqi, Muhammad Burhanudin; Fatmawati, Fatmawati; Aziz, Rahmat (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This research explores the effect of the safety corner method in increasing creativity in early childhood. With a qualitative case study approach, data collection is through observation and interviews with teachers and parents. The data analysis technique in this research uses a thematic analysis model. The population selection in this study used a purposive sampling technique. The results showed that the safety angle method significantly improved children's creative abilities, including fluency, flexibility, and originality. In addition, this method supports cognitive and social development by creating a structured yet flexible learning environment. Children who participate in safety corner learning show good adapting, collaborating, and independent thinking abilities compared to children in a conventional learning environment. However, challenges such as inconsistent implementation and difficulty in certain tasks were identified. This research contributes to the literature by highlighting the effectiveness of structured learning environments in encouraging creativity in early childhood and providing practical recommendations for educators.Â